Kualitas Buku Teks Bahasa Indonesia Kelas VII Terbitan Kemendikbud Kurikulum 2013 (Tinjauan Atas Aspek Kesesuaian) - Misriani, Agita (ESTETIK : Jurnal Bahasa Indonesia, 2018)
This study is aimed at describing the textbooks of class VII issued by Ministry of education and cultural of Indonesia (Kemendikbud), in terms of the compatibility of the content, language, presentation and layout. The data in this study consist of words, sentences, discourses and texts of the textbooks under examination, quoted from the main textbook issued by Kemendikbud as the learning source for student class VII. The instrument used in this study adopts BSNP standards. To analyze data, the study uses content analysis technique and to check the validity of the data it uses the technique of triangulation. As the results, it indicates that the Indonesian textbooks for class VII belong to appropriate category in terms of content, language and presentation. However, much revision is still needed especially on the accuracy of illustrations, conformity with the level of intellectual development of students and student accessibility and the completeness of the presentation based on its content. The suitability of layout reaches very appropriate category. It only needs to revise on the design of the cover performance in order to attract student’s interest. Keywords: Indonesian textbook, Indonesian language, class VII